The Governance of Religious Diversity - Attaftazani, Muhammad Ikhsan (Muslim Politics Review, 2023)
Routledge Handbook on the Governance of Religious Diversity. Edited by Anna Triandafyllidou and Tina Magazzini, London and New York: Routledge, 2021, xix+327pp, $ 52.95, ISBN: 978-0-367-53826-2 The Routledge Handbook on the Governance of Religious Diversity examines state-religion relations in more than 20 countries across the world. It particularly looks at how these states manage religious diversity. This book discusses that, in ancient times, empires and kingdoms, which were the embodiment of the states, used religion as a tool to control people. In modern times, many countries have become more secularized, hence the role of religion as a tool of control has diminished. States increasingly neglect the role of religion and religious people in society. This book argues that states with secularist ideology still need to pay attention to the role of religion in society.